Impact of the Russian Military Invasion on Ukraine’s Agriculture and Trade - Broyaka, Antonina (2023)
Antonina Broyaka POLICY SEMINAR Food System Repercussions of the Russia-Ukraine War 2023 Borlaug Dialogue Breakout session Co-organized by IFPRI and CGIAR OCT 26, 2023 - 1:10 TO 2:10PM EDT